Strategies for Urbanization and Economic Competitiveness in Burundi - World Bank Group (World Bank, Washington, DC, 2015)
This report argues that urbanization brings significant opportunities for both rural and urban areas and that Burundi needs to prioritize issues of economic growth and job creation. Based on a diagnostic evaluation of the current urbanization and spatial growth, GDP, and job potential, the report highlights the importance of prioritizing policies and investments to address deficiencies in Burundi urbanization. These remedial actions will help prepare Burundi for coming urban growth and help leverage agglomeration effects, minimize negative externalities associated with rapid urbanization, and potentially reap the demographic dividend of this transition. Getting urbanization right will need to be associated with targeted implementation strategies for growth in the agribusiness and tourism sectors. A rapid move to cities is a central element of Burundi development strategy, including an increase in the urbanization rate from 11 percent to 40 percent by 2025. Burundi vision 2025 aims to aims to promote urbanization via rural-urban migration, freeing arable land, providing nonagricultural urban employment opportunities, and in turn, reducing the risks for social conflict and economic fragility. This report shows that while the Vision 2025 target of rate 40 percent is unrealistic, Burundi urbanization rate may already be higher than expected due to limitations in the current urban classification and the agglomeration of households along major transport corridors. This uncertainty further underlines the need for government to address the key issues that will affect whether Burundi will achieve effective urbanization or not.